PENGARUH DANA BAGI HASIL, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP TAX EFFORT (Studi pada Pemerintah Kabupaten di Madura) - Subhan Subhan (Universitas Muhammadiyah Aceh, 2017)
The purpose of this reseach was to know the effect of profit sharing, general allocation fund and special allocation fund to tax effort in the district in madura. Independence variable in this reseach were profit sharing, general allocation fund and special allocation fund. Dependent variable of this reseach was tax effort.The data of this research is quantitative data in the form of financial statements of Regional Government and Gross Regional Domestic Product of 2010 until 2014. While the analytical model used to test the hypothesis is multiple linear regression is based on the financial statements of Regional Government and Regional Gross Regional Domestic Product until 2014.The results show that the profit-sharing fund, general allocation fund and allocation fund partially does not affect the tax effort. Simultaneously for revenue sharing, general allocation funds and allocation funds Partially no effect on tax effort.Â Key Word : Profit Sharing, General Allocation Fund, Special Allocation Fund, Tax Effort